2018
DOI: 10.1044/2018_lshss-17-0105
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Summaries of Narrative and Expository Discourse: Differences and Predictors

Abstract: https://doi.org/10.23641/asha.6167879.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 57 publications
1
7
0
2
Order By: Relevance
“…Tasks from two broad categories are generally used to study expository discourse production: (1) generation tasks—in which children produce an expository sample on a given topic without first hearing a model and (2) retell/summarization tasks—in which children are presented with an expository model and then are asked to retell or summarize the information. Lundine and colleagues 8 proposed that, in fact, retell and summarization tasks should be considered separately, due to the presumed increased cognitive demand of summarizing (e.g., participant-generated organization of information, incorporation of new facts with prior knowledge) versus retelling (e.g., imitation of the structure/organization of the expository model, restating given information).…”
Section: Measuring Expository Discourse Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tasks from two broad categories are generally used to study expository discourse production: (1) generation tasks—in which children produce an expository sample on a given topic without first hearing a model and (2) retell/summarization tasks—in which children are presented with an expository model and then are asked to retell or summarize the information. Lundine and colleagues 8 proposed that, in fact, retell and summarization tasks should be considered separately, due to the presumed increased cognitive demand of summarizing (e.g., participant-generated organization of information, incorporation of new facts with prior knowledge) versus retelling (e.g., imitation of the structure/organization of the expository model, restating given information).…”
Section: Measuring Expository Discourse Skillsmentioning
confidence: 99%
“…In some studies, participants are shown a video or lecture related to an academic topic and are then asked to retell or summarize the lecture. 6 8 12 Personal conflict resolution (PCR) tasks have also been used, in which scenarios are presented that contain a conflict between characters. The child is asked to summarize and interpret the conflict and then provide logical solutions.…”
Section: Measuring Expository Discourse Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…요약하기는 다시 말하기(retelling) 이상 의 능력을 필요로 한다. 다시 말하기 과제는 들은 내용의 구조를 단 기기억과 장기기억 속에 가능한 잘 저장했다가 인출하는 것이라면 (Lundine et al, 2018), 요약하기는 텍스트에 대한 표상을 구축해야 하는 좀 더 높은 수준의 인지처리과정을 거쳐야 한다 (Westby et al, 2010 (Graesser & Li, 2013). 특 히, 정보전달을 목적으로 하는 설명담화에서는 이러한 결속표지를 적절하게 사용하여 글의 구조가 잘 드러나도록 표현해야 한다 (Yoon, 2008 (Westby et al, 2010).…”
Section: 지금까지의 학령기 설명담화에 대한 선행연구들은 설명담화의unclassified
“…설명담화를 이해하고 표현하는 과정은 복잡하고 높은 수준의 인지처리과정을 거쳐야 한다 (Lundine et al, 2018;Westby, Culatta, Lawrence, & Hall-Kenyon, 2010 (Ray & Meyer, 2011). 설명담화 구조에 대한 인식이란 설명담 화가 어떻게 논리적으로 조직되었는지를 아는 것이다 (Meyer & Rice, 1982).…”
unclassified